Drinking Water Sources Feasibility Test Based On Escherichia Coli As an Indicator Of Pollutant In Sultan Village Stunting Locus Of - Fibrinika Tuta Setiani; Anang Kurniawan (International Journal of Public Health, 2024)
Introduction: Water quality parameters are indicated by the presence of E. coli bacteria. These bacteria come from human feces, warm-blooded animals, and non-fecal coliforms. Decree of the Health Minister of the Republic of Indonesia Number 907/MENKES/VII/2002 concerning requirements and supervision of drinking water quality states that good drinking water has a zero total coliform and fecal coliform. Methods: This research uses a descriptive approach with a cross-sectional design. It aims to determine the quality of water sources in Sulkatan village. Ten (10) water sources were used as the samples using total sampling method. The collected samples were then taken to the laboratory to be tested with a series of MPN tests Results and Discussion: The results show that the amount of Escherichia coli bacteria in water samples in Sulkatan Village is 0MPN/100 ml. It is owing to the location of the water source that is far from industrial activities, household waste and residential areas. Conclusion: The quality of the tested well-water samples is good and within normal limits in accordance with the Decree of the Health Minister of the Republic of Indonesia Number 907/MENKES/VII/2002